Rancang Bangun Sistem Informasi Helpdesk Berbasis Web pada PT. Dirgantara Indonesia - Iskandar, Fedrian Malik; Cahyono, Yono (Program Studi Teknik Informatika Universitas Pamulang, 2022)
Helpdesk is a complementary part of a service function, and is responsible as a source of solving problems or other issues, but problems at PT. Dirgantara Indonesia (Persero) is still the manual IT helpdesk system for data collection and recording of reports on hardware and software repair services as well as requests for computer supplies that complicate employee productivity. The lack of good work productivity is thought to be due to the inadequate IT helpdesk system for data collection and recording of reports on hardware & software repair services and requests for computer supplies. This research was made using the waterfall method and the analysis was carried out by means of interviews and system surveys that were running and data collection was carried out to obtain the required information. The design method focuses on developing models using the UML (Unified Modeling Language) model such as Use case diagrams. Sequence Diagram s, Activity Diagrams and Class Diagrams. The results of applying the method in developing the IT helpdesk application are that it can simplify the process of documenting applications from the start to the creation of an application. So that it can help the company in providing comfort for employees and simplify and speed up the company in data collection and recording of hardware & software repair service reports and requests for computer supplies